EFFORTS TO IMPROVE STUDENT LEARNING CREATIVITY IN PHYSICS LEARNING USING PROJECT-BASED LEARNING MODELS - Putri Maison, Puji Liani; Kurniawan, Dwi Agus; Milyani, Vetty (Journal of Learning and Technology in Physics, 2024)
This study aims to find out what are the efforts to increase creativity in physics learning by using a project-based learning model. This study uses a descriptive method with a qualitative approach and uses data collection techniques in the form of field studies and literature studies. Based on observations on physics learning at SMA Negeri 5 Batanghari, especially class X Science, it was analyzed by comparing the results of the initial study and literature study so that the results and conclusions of the study showed that the Project Based Learning model could improve student learning outcomes, creativityKeywords: Creativity, Physics Learning, Project Based Learning